2001
DOI: 10.1034/j.1600-0420.2001.790312.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials in relation to visual acuity in macular disease

Abstract: Results: Patients with macular disease produced significant delay of P100 latency and amplitude attenuation of the steady-state VECP, as compared with healthy subjects. P100 latency delay was less in patients with macular disease than in those with optic neuritis, while the attenuation rate of the steady-state VECP amplitude was similar between groups. Visual acuity was correlated with P100 latency and steady-state VECP amplitude reduction. Conclusions: Although the delay of latency was less in patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…Bass et al [14] also reported a delay in eyes with macular disease and concluded from their findings that a delay alone should not be used to differentiate between macular and optic nerve disease. In agreement, Ueda [15] and Negishi [16] reported that the pVEPs of patients with macular diseases, e.g., age-related macular degeneration, central serous chorioretinopathy, branch retinal vein occlusion, and branch retinal artery occlusion, were significantly longer and the amplitudes were significantly smaller than that of healthy subjects. They concluded that pVEPs can be of diagnostic value even at the retinal level.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Bass et al [14] also reported a delay in eyes with macular disease and concluded from their findings that a delay alone should not be used to differentiate between macular and optic nerve disease. In agreement, Ueda [15] and Negishi [16] reported that the pVEPs of patients with macular diseases, e.g., age-related macular degeneration, central serous chorioretinopathy, branch retinal vein occlusion, and branch retinal artery occlusion, were significantly longer and the amplitudes were significantly smaller than that of healthy subjects. They concluded that pVEPs can be of diagnostic value even at the retinal level.…”
Section: Discussionmentioning
confidence: 69%
“…Pattern visual evoked potentials (pVEPs) are used to assess the physiological condition of the visual system in patients with optic nerve [10][11][12] and retinal diseases [13][14][15][16]. In ERM, there are several reports about preoperative changes in pVEPs to predict visual outcome after surgery [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators7,9,10 have reported that retinal diseases may cause an increase in the pVEP latency, and the increase was significantly less for eyes with macular diseases than that in eyes with optic neuropathy. Shimada et al10 concluded that the pVEPs appear to be more sensitive for optic nerve diseases than for macular diseases in patients with similar visual acuities.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the combined use of the two studies can offer considerable information concerning the integrity of the retina. 96 Leber's congenital amaurosis is a familial disorder that presents with progressive blindness during the first few years of life. It can predispose to night blindness owing to the degeneration of the rods, which are the receptors that function in the low-level light at dusk and at night.…”
Section: Retinal Lesionsmentioning
confidence: 99%